Suppressing kelvin–helmholtz instability with an external magnetic field. (28th April 2020) - Sun, Wei; Zhong, Jiayong; Lei, Zhu; Zhang, Shu; Wang, Lifeng; Zhao, Kaige; An, Weiming; Ping, Yongli; Han, Bo; Yuan, Dawei; Tong, Bowei; Zhang, Qian; et al.
Abstract: We discuss the formation of a Kelvin–Helmholtz instability (KHI) produced by a laser-driven thin separate plastic (CH) foil plasma. The experimental design consists of magnetized plasma driven by intense laser irradiation and a small cylindrical permanent magnet. By comparing situations with and without an external magnetic field, we found that the KHI showed different rolling features which could be effectively suppressed by an external magnetic field. A quantitative analysis shows the consistency between the experiments and theory.